Success rate of nonsurgical endodontic treatment of nonvital teeth with variable periradicular lesions - Moazami, Fariborz; Sahebi, Safoora; Sobhnamayan, Fereshte; Alipour, Abbas (Iranian Endodontic Journal, 2011)
INTRODUCTION: Bacterial infection of tooth pulp can progress into periapical diseases. Root canal treatment has been established as the best treatment. In cases of failure, nonsurgical retreatment of teeth is preferred to surgical procedure and extraction. MATERIALS & METHODS: In this historical cohort study, 104 permanent teeth with apical lesion were treated during 2002-2008. All teeth showed radiographic evidence of periapical lesion varying in size from 1 to >10mm. A total of 55 teeth were treated with initial root canal treatment and 49 teeth required retreatment. Patients were recalled up to ≈7 years. All radiographs were taken by RSV MAC digital imaging set and long cone technique. The presence/absence of signs and symptoms and periapical index scores (PAI) were used for measuring outcome. Teeth were classified as healed (clinical/radiographic absence of signs and symptoms) or diseased (clinical/radiographic presence of signs and symptoms). The data were statistically analyzed using student t-test and Pearson chi-square or fisher’s exact test. RESULTS: The rate of complete healing for teeth with initial treatment was 89.7%, and for retreatment group was 85.7%; there was no significant difference. Size of lesions did not significantly affect the treatment outcomes. Success of tooth treatment did not reveal significant correlation with gender and number of roots. CONCLUSION: Orthograde endodontic treatment/retreatment demonstrates favorable outcomes. Thus, nonsurgical endodontic treatment/retreatment should be considered as the first choice in teeth with large periapical lesion.